2013
DOI: 10.1161/hypertensionaha.113.01382
|View full text |Cite
|
Sign up to set email alerts
|

Role of Axl in Early Kidney Inflammation and Progression of Salt-Dependent Hypertension

Abstract: The Gas6/Axl pathway regulates many cell functions and is implicated in hypertension. In this study we aimed to investigate the role of Axl in immune cells on initiation and progression of salt-dependent hypertension. Deoxycorticosterone-acetate (DOCA; 75mg/60days release) and salt hypertension was induced for 1week or 6weeks in Axl chimeras generated by bone marrow (BM) transplant to restrict Axl deficiency to hematopoietic or non-hematopoietic compartments. Depletion of Axl in hematopoietic cells (Axl−/− →Ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 25 publications
5
27
0
Order By: Relevance
“…Similar to our report in Axl chimeras 15 , we found reduction in arterial expression of IFN-γ (and Th1-dependent pathways) in Axl −/− mice after 6 weeks of DOCA-salt (not shown). We performed adoptive transfers of CD4 + T cells from Axl +/+ or Axl −/− to Rag1 −/− mice and compared BP changes after DOCA-salt to that in Rag1 −/− injected with PBS (PBS→Rag1 −/− ) or Axl +/+ mice (Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to our report in Axl chimeras 15 , we found reduction in arterial expression of IFN-γ (and Th1-dependent pathways) in Axl −/− mice after 6 weeks of DOCA-salt (not shown). We performed adoptive transfers of CD4 + T cells from Axl +/+ or Axl −/− to Rag1 −/− mice and compared BP changes after DOCA-salt to that in Rag1 −/− injected with PBS (PBS→Rag1 −/− ) or Axl +/+ mice (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Specifically, our group showed that Axl-dependent signals control vascular smooth muscle cells survival and promote vascular remodeling after 6 weeks of DOCA-salt 13 . We recently reported that Axl expression in bone marrow (BM)-derived cells is responsible for early and late phases of DOCA-salt hypertension 15 . Adaptive immune cells such as T lymphocytes contribute to vascular dysfunction and DOCA-salt hypertension 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Renal Axl expression having a protective function in kidney pathology is also consistent with a recent report examining the role of haematopoietic and non-haematopoietic Axl in DOCA salt-induced hypertension and kidney dysfunction [29]. This study demonstrated that while haematopoietic Axl had a pathological role in the model, non-haematopoietic Axl protected against renal reactive oxygen species production [29].…”
Section: Discussionsupporting
confidence: 91%
“…Data analyses were done using a web-based suite at SABiosciences (Qiagen). We used the curated InnateDB resource for pathway analyses as we have previously described (1,8).…”
Section: Methodsmentioning
confidence: 99%